Sistema para conectar clientes a prestadores de serviço - TEIXEIRA, Guilherme Borges; SOUZA, Lucas Gonçalves de; CHAVES, Matheus Fonseca; SOUZA, Myke Raphael Oliveira de; SILVA, Wendy Stefani Cristine da (143, 2022)
COVID-19 has caused significant consequences around the world and during this journey all companies, regardless of size, have had to face serious challenges. Due to the precariousness of work, the main services that had to reinvent themselves were the informal services, the autonomous ones. The occupation structure of the labor market by these professionals is a socially significant phenomenon and, given these circumstances, the objective of this project is the development and documentation of an application for mobile devices, with web integration to connect clients and informal service providers, allowing the dissemination of services by providers and the search for them by users, in a simple and objective way. The results of this project had the development of an application available for mobile device, compatible with Android, this software will be able to make a bridge/connection between users being these: service providers and their customers. In the future, the application may be improved to adapt to the needs and experiences of your consumer with your service provider.
System to connect customers to service providers
A COVID-19 Causou sequelas significativas no mundo todo e no meio desse percurso todas as empresas, independentemente do tamanho, tiveram que enfrentar sérios desafios. Devido à precarização do trabalho, os principais serviços que tiveram que se reinventar foram os serviços de informalidade, os autônomos. A estrutura de ocupação do mercado de trabalho por esses profissionais constitui um fenômeno significativo socialmente e dado essas circunstâncias o objetivo deste projeto é o desenvolvimento e a documentação de um aplicativo para dispositivos móveis, com integração à web para conectar clientes e prestadores de serviço informais, permitindo a divulgação dos serviços pelos prestadores e a busca por esses pelos usuários, de maneira simples e objetiva. Os resultados desse projeto tiveram como desenvolvimento um aplicativo disponível para dispositivo móvel, compatível com Android, este software poderá realizar uma ponte/conexão entre os usuários sendo estes: prestadores de serviço e seus clientes. Futuramente o aplicativo poderá ser aperfeiçoado de forma a se adequar às necessidades e experiências do seu consumidor com seu prestador de serviço.
Keywords: Desenvolvimento de software; Serviço ao cliente; Informação e Comunicação